Aspek-Aspek Arsitektur Kolonial Belanda Pada Bangunan Pendopo Puri Mangkunegaran Surakarta - S Samsudi; Agung Kumoro W; Dyah Susilowati Pradnya Paramita; Anita Dianingrum (Universitas Sebelas Maret Surakarta, 2020)
Dutch colonial architecture that developed in Indonesia, throughout the colonial period (around the 17th century to 1942) was a combination of colonial and local culture to respond to the Indonesian climate. Dutch colonial architecture in Indonesia is a work of Dutch colonial heritage in Indonesia during the colonial period. The result was the Dutch East Indies style with a